Microstructure, dielectric, ferroelectric and piezoelectric properties of NbO3 lead-free ceramics prepared via cold sintering with post-annealing - Neng Qin; Xiao-Ming Chen; Xin-Yu Huang; Jia-Jun Lan; Yu-Ding Xu; Li-Na Liu; Han-Li Lian; Peng Liu (Journal of Advanced Dielectrics, 2025)
Via the method of cold sintering with post-annealing, the lead-free ceramics [Formula: see text][Formula: see text][Formula: see text]NbO3 were prepared. The cold sintered pellet without post-annealing shows a relative density ([Formula: see text] of 77.9%, which is larger than [Formula: see text] of the green pellet via the conventional solid-state sintering (SSS) method ([Formula: see text]). The cold sintered pellets were post-annealed at temperatures between [Formula: see text]C and [Formula: see text]C. The effect of post-annealing temperatures on microstructure, dielectric, ferroelectric and piezoelectric properties of the ceramics was studied in detail. After being post-annealed, the relative densities and grain sizes of the ceramics were increased. The ceramics post-annealed at [Formula: see text]C show excellent dielectric, ferroelectric and piezoelectric properties. Compared to the conventional SSS method, the method of cold sintering with post-annealing is successful in preparing dense [Formula: see text][Formula: see text][Formula: see text]NbO3 lead-free ceramics in a wide temperature range and at relatively low temperatures.